Implementasi Hidden Text dengan Algoritma Blowfish dan Kompresi Huffman dalam Security Dokumen - Siti Muryanah; Diah Rahmawati (Universitas Singaperbangsa Karawang, 2023)
Technological developments have positive and negative impacts for users. Information is easily and quickly accessed by anyone, anytime and anywhere. To maintain security, an effort is needed to secure information from unauthorized parties. Cryptography and steganography as a way to maintain the security of this information. The information we have (plain text) will be converted into random or hard-to-understand information (cipher text), commonly known as encryption. Furthermore, the random information will be hidden or inserted into the digital image (encoded) so that it will not make other people suspect that the digital image contains information that is being hidden. In a digital image that has been inserted with confidential information (stego image), there is no difference of visual man either before or after inserting the confidential information. This research succeeded in securing information in the form of documents in pdf, xlsx, docx, pptx and txt formats using Blowfish cryptography and LSB Steganography. The size of the document resulting from the encryption process becomes smaller with the Huffman compression process with an average value of 57% of the original document. The test uses 3 different files and 3 images in each file format, namely pdf, xlsx, docx, pptx and txt. Tests on stego images produce high quality with an MSE value of 0.092 and a PSNR of 57.12 dB.